Tuberculosis and latent infection in employees of different prison unit types - Péricles Alves Nogueira; Regina Maura Cabral de Melo Abrahão; Vera Maria Neder Galesi; Rossana Verónica Mendoza López (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE Estimate the prevalence of active tuberculosis and latent tuberculosis infection among the staff that is in contact and the staff that is not in contact with prisoners, and investigate factors associated with latent tuberculosis infection in this population. METHODS Observational cross-sectional study, conducted from 2012 to 2015, in employees of different prison units in the municipality of Franco da Rocha, SP. It consisted of the application of a questionnaire, application and reading of the tuberculin test, sputum smear microscopy, sputum culture, and radiological examination. The association between the qualitative variables was calculated by the Pearson's chi-squared test. The sociodemographic and clinical-epidemiological factors related to the latent tuberculosis infection were evaluated by the logistic regression with the odds ratios (OR) calculation and their respective intervals with 95% of confidence (95%CI). RESULTS A total of 1,059 employees were examined, 657 (62.0%) of prisons, 249 (23.5%) of CASA Foundation units and 153 (14.5%) of custodial and psychiatric treatment hospitals. The tuberculin test was applied and read for 945 (89.2%) professionals. Of these, 797 (84.3%) were contacts of detainees and 148 (15.7%) were not. Among prison staff, the factors associated with latent tuberculosis infection were: contact with detainee (OR = 2.12, 95%CI 1.21-3.71); male gender (OR = 1.97, 95%CI 1.19-3.27); between 30 and 39 years old (OR = 2.98, 95%CI 1.34-6.63), 40 to 49 years old (OR = 4.32, 95%CI 1.94-9.60), and 50 to 59 years old (OR = 3.98, 95%CI 1.68-9.43); nonwhite color or race (OR = 1.89, 95%CI 1.29-2.78); and smoker (OR = 1.64, 95%CI 1.05-2.55). There were no positive test on sputum smear microscopy and culture. Of the 241 (22.8%) professionals who underwent radiological examination, 48 (19.9%) presented alterations of which 11 were suspected of tuberculosis. CONCLUSIONS Prison employees who have direct contact with detainees are 2.12 times more likely to become infected with Mycobacterium tuberculosis in the work environment and consequently to become ill with tuberculosis and should be targeted for disease prevention and control.